2006
DOI: 10.1038/sj.bjc.6603333
|View full text |Cite
|
Sign up to set email alerts
|

Do delays between diagnosis and surgery in resectable oesophageal cancer affect survival? a study based on West Midlands cancer registration data

Abstract: This retrospective study investigates if delays between the diagnosis of cancer of the oesophagus and surgical resection influence long-term survival. Data held by the West Midlands Cancer Intelligence Unit on 800 patients who underwent oesophagectomy for a diagnosis of cancer of the oesophagus or oesophagogastric junction between 1995 and 2000 were reviewed. Six hundred and thirtytwo patients treated with curative intention and who had not received neo-adjuvant treatment in the form of radio-or chemotherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
5
20
0
Order By: Relevance
“…Surprisingly, it appeared that overall survival was improved in patients with a longer hospital delay, although this difference was not statistically significant. This is in line with the results of Kötz et al10 who showed that a longer delay between diagnosis and surgical resection was associated with improved survival in esophageal cancer patients. However, the delay between diagnosis and surgery was not an independent prognostic variable on multivariate analysis in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, it appeared that overall survival was improved in patients with a longer hospital delay, although this difference was not statistically significant. This is in line with the results of Kötz et al10 who showed that a longer delay between diagnosis and surgical resection was associated with improved survival in esophageal cancer patients. However, the delay between diagnosis and surgery was not an independent prognostic variable on multivariate analysis in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Our group has reported a 5‐year overall survival rate of 20% in patients undergoing surgery for adenocarcinoma, while we found a 5‐year survival rate of 33% in SCC patients. This difference is similar to some studies 4,6,11 but at variance with others 3,5,12 . The reasons for this difference are not obvious although the previously mentioned review found a better 5‐year survival with SCC in Western countries (30 versus 27%) but the opposite in Eastern countries (34 versus 37%) 9 .…”
Section: Discussionsupporting
confidence: 84%
“…Patients treated with surgery alone have 5‐year survival rates of 12–27% in all 6,12,14–16 but a few 4,17 series where it was as high as 32%. In contrast, Mariette et al.…”
Section: Discussionmentioning
confidence: 99%
“…Delay between diagnosis and surgical treatment of endometrial cancer may result in worsened overall survival, potentially as a consequence of disease progression or difficulty accessing care. 1 A relationship between surgical delay and survival disadvantage has been demonstrated in breast, 2,3 rectal, 4 and bladder 5 cancers; this relationship does not clearly exist for esophageal, 6 gastric, 4 renal cell, 7 or cervical 8 cancers. For endometrial cancer, findings to date have been mixed.…”
Section: Introductionmentioning
confidence: 99%